A comparative handbook to the Gospel of Mark comparisons with Pseudepigrapha, the Qumran Schrolls [sic], and Rabbinic literature - Chilton, Bruce 1949-; Bock, Darrell L. 1953-; Gurtner, Daniel M. 1973- (Leiden [Netherlands] Boston Brill, 2010)
This handbook addresses the Judaic context of the Gospel according to Mark. Mark's text is compared to distinct categories of writings, Pseudepigrapha (together with Philo and Josephus), discoveries related to Qumran, Rabbinic Literature (as well as the Targumim), and examples of Aramaic language that reflect first-century usage
Preface -- Introduction -- Apocrypha, Pseudepigrapha, Philo, and Josephus -- The Dead Sea Scrolls -- The Rabbinic Canon -- The Targumim -- Aramaic retroversion -- According to Mark -- Appendices I: Rabbinic rules of interpretation -- II: (The) Son of (the) Man, and Jesus -- III: Rabbi as a title of Jesus -- IV: Synagogues.
Includes bibliographical references and indexes
Electronic reproduction; Available via World Wide Web
Online-Ausg.
Keywords: Bible -- Criticism, interpretation, etc